Antibacterial Effects of Parmelia sulcata and Hypogymnia tubulosa Acetone_x000D_ Extracts Against Isolates From Soak Liquors - (:unkn) unknown (My University, 2020)
It is well known that there are halophilic or non-halophilic bacteria in salt, soak liquors, salted and soaked hides/skins in highnumbers in the leather industry. These bacteria have several hydrolytic enzymes which cause irreversible defects on finishedleather product. Although antimicrobial agents are utilized to control the bacterial population in the soaking process, theseagents have not sufficient efficacy due to inadequate application of these agents or the presence of antimicrobial-resistantbacterial strains in soak liquors. In this respect, alternative agents or strategies may be helpful for controlling the bacterialpopulation. For this purpose, Bacillus toyonensis, B. mojavensis, B. subtilis, B. amyloliquefaciens, B. velezensis, B. cereusand B. licheniformis, which were isolated from soak liquor samples of different tanneries in the previous study, were tested inthe present study and the antibacterial effects of acetone extracts of Parmelia sulcata and Hypogymnia tubulosa wereevaluated on these isolates. The pure cultures of the isolates were confirmed by colony morphologies on agar plates andGram staining. Moreover, antibacterial activities for acetone extracts of Parmelia sulcata and Hypogymnia tubulosa againstthese isolates were tested at certain concentrations of 240, 120, 60 and 30 μg/ml. Hypogymnia tubulosa extracts were foundto be more successful in comparison to the extracts of Parmelia sulcata on tested isolates. These tested lichen species can beused to control the population of bacteria in the soaking process and also to prevent potential defects on the hide/skin thatmay be seen in subsequent tanning processes due to the development of these bacteria.

Deri endüstrisinde tuzda, tuzlanmış ve ıslatılmış büyükbaş ve küçükbaş hayvan derilerinde, ve ıslatma sıvılarında çok fazla_x000D_ sayıda halofil veya halofil olmayan bakterilerin bulunduğu bilinmektedir. Bu bakteriler bitmiş deri ürününde geri dönüşümü_x000D_ olmayan kusurlara neden olan birkaç hidrolitik enzime sahiptir. Islatma işleminde bakteri popülasyonu kontrol etmek için_x000D_ antimikrobiyal ajanların kullanılmasına rağmen, bu ajanların yetersiz uygulanmalarına veya ıslatma sıvılarında_x000D_ antimikrobiyallere dirençli bakteri suşlarının bulunmasına bağlı olarak yeterli etkinliğe sahip değillerdir.Bu bağlamda,_x000D_ bakteri popülasyonunu kontrol etmek için alternatif ajanlar veya stratejiler yardımcı olabilir. Bu amaçla, bir önceki çalışmada_x000D_ farklı tabakhanelerden toplanan ıslatma çözeltisi örneklerinden izole edilen Bacillus toyonensis, B. mojavensis, B. subtilis, B._x000D_ amyloliquefaciens, B. velezensis, B. cereus ve B. licheniformis test edilmiştir ve Parmelia sulcata ve Hypogymnia_x000D_ tubulosa'nın aseton özütlerinin antibakteriyel etkileri bu izolatlar üzerinde değerlendirilmiştir. İzolatların saf kültürleri, agar_x000D_ plakaları üzerinde koloni morfolojileri ve Gram boyamaları ile doğrulanmıştır. Ayrıca, Parmelia sulcata ve Hypogymnia_x000D_ tubulosa'nın aseton özütlerinin bu izolatlar üzerine antibakteriyel aktiviteleri, 240, 120, 60 ve 30 μg/ml konsantrasyonlarında_x000D_ test edilmiştir. Hypogymnia tubulosa özütlerinin Parmelia sulcata özütlerine kıyasla test edilen izolatlar üzerinde daha_x000D_ başarılı olduğu bulunmuştur. Bu test edilen liken türleri, ıslatma işleminde bakteri popülasyonunu kontrol etmek için ve_x000D_ ayrıca ileriki tabaklama işlemlerinde bu bakterilerin gelişimine bağlı olarak görülebilecek deri üzerindeki potansiyel kusurları_x000D_ engellemek amacıyla kullanabilir.
Parmelia sulcata ve Hypogymnia tubulosa Aseton Özütlerinin Islatma Sıvılarından Elde Edilen İzolatlar Üzerine Antibakteriyel Etkileri